Inflammatory Biomarkers in the Diagnosis and Prognosis of Rheumatoid Arthritis–Associated Interstitial Lung Disease - Mena-Vázquez, Natalia; Godoy-Navarrete, Francisco Javier; Lisbona-Montañez, José Manuel; Redondo-Rodríguez, Rocío; Manrique-Arija, Sara; Rioja, Jose; Mucientes, Arkaitz; Ruiz-Limón, Patricia; García-Studer, Aimara; Ortiz-Marquez, Fernando; Oliver-Martos, Begoña; Cano-García, Laura; et al. (MDPI, 2023)
This study aimed to identify inflammatory factors and soluble cytokines that act as biomarkers in the diagnosis and prognosis of rheumatoid arthritis-associated interstitial lung disease (RAILD). We performed a nested prospective observational case–control study of patients with RA-ILD matched by sex, age, and time since the diagnosis of RA. All participants underwent pulmonary function testing and high-resolution computed tomography. ILD was defined according to the criteria of the American Thoracic Society/European Respiratory Society; the progression of lung disease was defined as the worsening of FVC > 10% or DLCO > 15%. Inflammation-related variables included the inflammatory activity measured using the DAS28-ESR and a multiplex cytokine assay. Two Cox regression models were run to identify factors associated with ILD and the progression of ILD. The study population comprised 70 patients: 35 patients with RA-ILD (cases) and 35 RA patients without ILD (controls). A greater percentage of cases had higher DAS28-ESR (p = 0.032) and HAQ values (p = 0.003). The variables associated with RA-ILD in the Cox regression analysis were disease activity (DAS28) (HR [95% CI], 2.47 [1.17–5.22]; p = 0.017) and high levels of ACPA (HR [95% CI], 2.90 [1.24–6.78]; p = 0.014), IL-18 in pg/mL (HR [95% CI], 1.06 [1.00–1.12]; p = 0.044), MCP-1/CCL2 in pg/mL (HR [95% CI], 1.03 [1.00–1.06]; p = 0.049), and SDF-1 in pg/mL (HR [95% CI], 1.00 [1.00–1.00]; p = 0.010). The only variable associated with the progression of ILD was IL-18 in pg/mL (HR [95% CI], 1.25 [1.07–1.46]; p = 0.004). Our data support that the inflammatory activity was higher in patients with RA-ILD than RA patients without ILD. Some cytokines were associated with both diagnosis and poorer prognosis in patients with RA-ILD.
Keywords: Marcadores bioquímicos; Artritis reumatoide; Rheumatoid arthritis; Interstitial lung disease; Biomarkers; Cytokines; Morbidity; Inflammation